Analysis Of Capital, Asset Quality, Management, Earnings, and Liquidity (CAMEL) on the Financial Performance of PT Bank Rakyat Indonesia (Persero) Tbk for the 2020-2024 Period - Anisa Permata; Ramadhan Harahap; Pipit Buana Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk from 2020 to 2024 using the CAMEL method, which consists of five aspects, namely Capital, Asset Quality, Management, Earnings, And Liquidity. This research uses a qualitative approach with a descriptive research type. The data collection technique used is documentation taken from documents for the 2020-2024 period available on the official website of Bank Rakyat Indonesia. The results of the study on the financial performance of PT Bank Rakyat Indonesia Persero Tbk for the period 2020-2024 are in the healthy category and it can be concluded that the performance is in good and relatively stable condition despite the economic pressure caused by the COVID-19 pandemic and the post-pandemic recovery period. This study is expected to contribute to bank management in decision making and serve as a reference for further research in the banking sector.